Religion, Leadership and School Principals; Symbolic Interactionism Perspective - Asmuri, Asmuri; Zakaria, Gamal Abdul Nasir; Palawa, Alimuddin Hassan; Rahman, Rahman (JURNAL AL-TANZIM, 2022)
This study aims to analyze the leadership behavior of the madrasa principal in internalizing the religious values of the symbolic interactionalism perspective in the madrasa. This research was conducted using a phenomenological type of qualitative approach, in which researchers used interviews, observations, and documentation to obtain data in the field. The data analysis was carried out circularly through data presentation, data reduction, and concluding. The results showed that the leadership behavior of the madrasa principal in internalizing religious values from the symbolic interactionalism perspective was reflected in ritual practices as religious symbols that were displayed personally and collegially. In addition, sincerity is used as the basis for his perpetuation at the madrasa. This study implies that religious values must be internalized in every managerial activity in the madrasa to achieve the desired goals.